Managerial Performance Improvement Strategy Based on Budget Participation - Aprih Santoso; Andre S Nugroho (INDEF - Institute for Development of Economics and Finance, 2020)
Regional autonomy has led to the decentralization of health services. The impact of the decentralization of health services is the emergence of differences between provinces and districts/cities in terms of the status of funding sources and changes in the structure of the health system in the regions. The main purpose of this study is to examine the relationship between budgetary participation and managerial performance in a public sector organization. It also attempts to examine whether organizational commitment and perception of innovation mediate the budgetary participation and performance relationship. As one of the government-owned public sector organizations in charge of health issues, Semarang City Health Office became the public spotlight regarding budget and performance. The study was conducted at Semarang City's Health Office, and all of the Public Health Centers, the sample size used is 60 echelon officers, using path analysis. The analysis results indicate that Budgetary participation affects managerial performance via the mediating variable of organizational commitment but not perception of innovation. There is a direct relationship between budgetary participation, managerial performance, organizational commitment, and perception of innovation Keywords: Budgetary, managerial performance, commitment, innovation, public sector. JEL Classification: H51, H61, R10